SURVEY AND STUDY OF GASTROINTESTINAL DISEASES - G.K. Rahmatullayeva; N.A. Axmedova; M.A. Ubaydullayeva (Scholar Express Journals, 2025)
According to the World Health Organization, gastrointestinal diseases cause more than 3 million deaths worldwide annually, accounting for 4-5% of all global deaths. Men die 38% more often from gastrointestinal diseases than women. Gastritis affects about half of the world's population. In 2013, approximately 90 million new cases were recorded. The likelihood of contracting the disease increases with age. In Uzbekistan, gastrointestinal diseases such as infections, gastritis, gastric ulcers, and pancreatitis are among the most common health issues.
Keywords: Gastritis; Pancreatitis; Peptic Ulcer Disease